Psychosocial analysis of fear of corrupt practices among university students: a case study of Olabisi Onabanjo University (2007)
The study investigated psycho-social analysis of fear of corrupt practices among students of Olabisi Onabanjo University. The study was a cross-sectional research which specifically adopted Ex-post facto design. Questionnaire format was utilized for data collection. The questionnaire included the Big-five personality inventory, fear of corrupt practices and personal data scales. Four (4) hypotheses were stated and tested using multiple regression analysis. The result showed that personality characteristics of extraversion, neuroticism, agreeableness, openness to experience and conscientiousness significantly and co-jointly predicted fear of corrupt practices {F(5,244) =4.48, P<.05,R2 =.08}. However, only personality traits of extroversion [a=-.17, t = 2.42, P<.05J and openness to experience [a=.23, t = 3.04, P<.05] had significant independent influence on fear of corrupt practices respectively. The results showed also that males and females were not significant different on fear of corrupt practices [t = -1.69, df= 248, P>.05J; student within the age group 18 - 30 years reported more fear of corrupt practices than students with the age group 31-45 years. The results showed further that students who had prior criminal victimization experience reported more fear of corrupt practices than student who had no prior criminal victimization [t = 2.94, df = 248, P<.01J; ordinary students were not significantly different on fear of corrupt practices, [t = -.056, df = 248, P>.05], Female and male who were political office holder were not significantly different on fear of corrupt practices [t = -1.15, df= 91, P>.05J. The study was concluded by establishing that some personality characteristic, specifically extraversion and openness to experience were found to have significant independent influence on fear of corrupt practices. Similarly, all the considered personality characteristics had significant co-joint influence on fear of corrupt practices. Age and prior victimization experience were found also to significantly influence fear of corrupt practices